2014
DOI: 10.1039/c4ob00860j
|View full text |Cite
|
Sign up to set email alerts
|

Thiomyristoyl peptides as cell-permeable Sirt6 inhibitors

Abstract: Sirtuins regulate a variety of biological pathways and inhibitors of sirtuins have been actively pursued as tool compounds to study sirtuin biology and as potential therapeutics. Here we demonstrate that thiomyristoyl peptides are potent and cell-permeable inhibitors of Sirt6, one of the seven human sirtuins, and will serve as starting point for the development of more specific Sirt6 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 34 publications
1
68
0
Order By: Relevance
“…Thioacyl lysine peptides can react with NAD in the sirtuin active site, forming a relatively stable intermediate that inhibits sirtuin (Figure 1A) (Fatkins et al, 2006; Hawse et al, 2008; Smith and Denu, 2007). Recent studies suggested that different sirtuins may have different acyl group specificity (Du et al, 2011; Feldman et al, 2013; et al, 2013a; Zhu et al, 2012), which can be utilized to design inhibitors specific for different sirtuins (He et al, 2012; He et al, 2014). To target the sirtuins that can recognize aliphatic acyl groups, we synthesized four thioacyl lysine compounds, TA (thioacetyl) (Suzuki et al, 2009), TB (thiobutyryl), TH (thioheptanoyl), and TM (thiomyristoyl) (Figure 1B), and then analyzed their ability to inhibit different sirtuins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thioacyl lysine peptides can react with NAD in the sirtuin active site, forming a relatively stable intermediate that inhibits sirtuin (Figure 1A) (Fatkins et al, 2006; Hawse et al, 2008; Smith and Denu, 2007). Recent studies suggested that different sirtuins may have different acyl group specificity (Du et al, 2011; Feldman et al, 2013; et al, 2013a; Zhu et al, 2012), which can be utilized to design inhibitors specific for different sirtuins (He et al, 2012; He et al, 2014). To target the sirtuins that can recognize aliphatic acyl groups, we synthesized four thioacyl lysine compounds, TA (thioacetyl) (Suzuki et al, 2009), TB (thiobutyryl), TH (thioheptanoyl), and TM (thiomyristoyl) (Figure 1B), and then analyzed their ability to inhibit different sirtuins.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, TM, but not M, increased the level of α-tubulin acetylation in MDA-MB-231 cells based on immunofluorescence imaging (Figure 4F). SIRT2 has been reported to be not only a deacetylase, but also a defatty-acylase (He et al, 2014; Liu et al, 2014), so we further examined the effect of TM on the defatty-acylase activity of SIRT2 in cells. Metabolic labeling of fatty-acylated proteins revealed that SIRT2 KD (Figure S4B) but not TM (Figure S4C) was able to elevate the fatty-acylation levels of many proteins, suggesting that in cells TM is a potent inhibitor of SIRT2 deacetylase but not defatty-acylase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from other groups and our own lab indicate that thiosuccinyllysine peptides inhibit SIRT5 55 and thiomyristoyllysine peptides inhibit SIRT6. 56 Based on the prototype probe 1, additional probes with thiosuccinyllysine and thiomyristoyllysine warheads were synthesized to target SIRT5 and SIRT6 (probe 5 and 6, Figure 6A). Indeed, probe 5 with the thiosuccinyl warhead selectively inhibits SIRT5 with an IC 50 of 3.2 ± 0.4 μ M (Table 1).…”
Section: Resultsmentioning
confidence: 99%